HEPN RNases – an emerging class of functionally distinct RNA processing and degradation enzymes. (2nd January 2021) - Pillon, Monica C.; Gordon, Jacob; Frazier, Meredith N.; Stanley, Robin E.
Abstract: HEPN (Higher Eukaryotes and Prokaryotes Nucleotide-binding) RNases are an emerging class of functionally diverse RNA processing and degradation enzymes. Members are defined by a small α-helical bundle encompassing a short consensus RNase motif. HEPN dimerization is a universal requirement for RNase activation as the conserved RNase motifs are precisely positioned at the dimer interface to form a composite catalytic center. While the core HEPN fold is conserved, the organization surrounding the HEPN dimer can support large structural deviations that contribute to their specialized functions. HEPN RNases are conserved throughout evolution and include bacterial HEPN RNases such as CRISPR-Cas and toxin-antitoxin associated nucleases, as well as eukaryotic HEPN RNases that adopt large multi-component machines. Here we summarize the canonical elements of the growing HEPN RNase family and identify molecular features that influence RNase function and regulation. We explore similarities and differences between members of the HEPN RNase family and describe the current mechanisms for HEPN RNase activation and inhibition.